Effect of shape and size of sampling window on the determination of average length, intensity and density of trace discontinuity - Sharifzadeh, Mostafa; Kamali, A.; Shahriar, K.; Aalianvari, A.; Esmaeilzadeh, A. (2016)
The fractures geometrical characteristics can be calculated by various sampling methods in 1 dimension (1D) & 2 dimensions (2D). The Discrete Fracture Network (DFN) simulation results show some of the equations are suitable for calculation of mean trace length and the difference between actual value and their values is less than 15%. Apparent density is dependent on scale, but the Mauldon's estimators are independent of scale despite the variation in fracture length. For all joint sets, the difference of apparent areal intensity by samplings windows and circular estimator is less than 5% proportionate to actual value. A reduction of Fisher constant doesn't have much effect on mean trace length of the fractures with length less than 1.5 m, but it results in a 21% difference for fractures with length longer than 1.5 m. Variation of this parameter affects the density, too and the difference can be 5% to 10% depending on fracture length. But, variation in Fisher constant doesn't have any effect on areal intensity for fractures with length less than 2 m.